Cyclic Voltammetric Measurements of Neurotransmitters. (1st January 2017) - Johnson, Justin A.; Wightman, R. Mark
Abstract : Electrochemical monitoring of neurotransmitter release, a central mechanism for neural communication, provides a powerful means of accessing sub-second information about this phenomenon. Robust interpretation of the electrochemical signals to access this information, however, requires careful consideration of the selectivity of measurements. Indeed, much of the evolution of the field over the forty years since its introduction has focused on development of and data analysis methods for improving this aspect of the measurements. Here, we present a brief overview of the advances that have enabled selective in vivo monitoring of single neurotransmitters and opened the door to using voltammetry to elucidate the role of neurotransmission in the behavior of awake and freely behaving animals.